Transactional leadership and organizational creativity: Examining the mediating role of knowledge sharing behavior - Syed Talib Hussain; Jaffar Abbas; Shen Lei; Muhammad Jamal Haider; Tayyaba Akram (Cogent Business & Management, 2017)
This study examines the role of transactional leadership in creating the organizational creativity through knowledge sharing behavior between employees and leaders. The study explores the contingent reward as for knowledge sharing for organizational creativity in organization, because many studies have been conducted for encouraging the knowledge sharing through contingent reward system. But this study explores whether contingent reward system through transactional behavior creates organizational creativity. So the data were collected from telecom sector. The total distribution was 360 and questionnaire was collected from 308 but usable questionnaires were 300. For data analysis the CFA and SEM tests were applied. The results showed that transactional leadership and knowledge sharing have positive relationship with creativity, and knowledge sharing is mediating the role between transactional leader and organizational creativity. The theoretical framework will be used for future research of this paper to foster the extrinsic reward as exchange for knowledge sharing and creativity.
Keywords: 650